THE INFLUENCE OF MEMORIZATION OF THE QUR’AN ON THE RELIGIOSITY OF THE FEMALE SANTRI OF THE STUDENT DORMITORY OF THE SUNAN PANDANARAN ISLAMIC BOARDING SCHOOL COMPLEX VI - Nur Laelatul Qodariyah; Yulia Nafa Fitri Randani (At-Thullab : Jurnal Mahasiswa Studi Islam, 2023)
The ability to memorize the Qur'an has a strong impact on memory. especially in terms of concentration. Every single verse he memorized was able to provide encouragement and motivation in his activities. Moreover, the Qur'an is a guide for Muslims, which we must protect and practice. Instead, the author provides two categories related to the level of religiosity in memorizing the Qur'an. The first is the habluminallah category, and the second is hablum minannas. In relation to habluminallah, it can be interpreted as the relationship of a memorizer of the Qur'an with Allah SWT. While hablum minannas relationships with fellow human beings. The object of this research is the female students of the Sunan Pandanaran Islamic Boarding School, Complex VI, where the majority of these Islamic boarding schools are memorizers of the Qur'an. While the research method used is qualitative, with data collection instruments in the form of interviews.